Nomogram for predicting postoperative clinical remission of hypertension in patients with adrenal tumors - YuanJian Liao; MingShun Zuo; YongPan Zhu; Te Xu; JiaJia Tang; LongMei Fan; Neng Zhang (Discover Oncology)
Abstract Objective Hypertension caused by adrenal tumors is a frequent cause of secondary hypertension. Treating primary adrenal disease can significantly improve or cure hypertension. However, hypertension may persist in some patients after surgery, leading to controversy over the choice of surgery or conservative treatment. The aim of this study is to construct and validate a model for predicting postoperative clinical remission of hypertension in patients with adrenal tumors to help surgeons make better surgical decisions. Patients and methods A retrospective analysis was conducted on data pertaining to 336 patients diagnosed with adrenal tumors and hypertension between January 1, 2012 and December 31, 2022. Potential predictor variables were utilized to develop a nomogram, which were internally validated using a bootstrap resampling method. Clinical data from 141 patients from January 1, 2023 to December 31, 2023 were analyzed for external validation using the same criteria. Results In patients with non-functioning adrenal tumors, lower age, body mass index, and hypertension grade were considered independent predictors of postoperative clinical remission of hypertension. In patients with functional adrenal tumors, absence of diabetes mellitus, lower systolic blood pressure, and duration of hypertension were considered independent predictors of postoperative clinical remission of hypertension. The area under the curve (AUC) for the nonfunctional adrenal tumor prediction model was 0.761, the AUC for internal validation using the bootstrap method (resampling = 1000) was 0.757, and the AUC for the external validation cohort was 0.837. The AUC for the functional adrenal tumor prediction model was 0.848, the AUC for internal validation using the bootstrap method (resampling = 1000) was 0.836, and the AUC for the external validation cohort was 0.836. The calibration curves demonstrated a satisfactory fit between the model and clinical utility, as evidenced by the decision curve analysis. Conclusion Nomograms have been demonstrated to perform well in predicting postoperative clinical remission of hypertension in patients with adrenal tumors. This may assist clinicians in distinguishing between patients with adrenal tumors who are likely to achieve clinical remission of hypertension after surgery at an early stage.